PENGARUH PEMASARAN POLITIK MEDIA SOSIAL DAN KUALITAS INFORMASI TERHADAP NIAT MEMILIH DENGAN KEPERCAYAAN DAN LOYALITAS PEMILIH SEBAGAI MEDIASI - Alim, Ikhwan Nur; Herdian Farisi; Yuliana, Ade (Jurnal Manajemen & Bisnis Jayakarta, 2024)
This study seeks to determine how political marketing social media and information quality impact generation Z's voting intentions, using voter trust and loyalty as mediators. This study employed a quantitative approach, with 100 respondents selected by purposive selection. Data analysis shows that political marketing on social media increases voter trust and loyalty. The quality of information also has a positive impact, as greater quality information increases voters' confidence and trust, which can result in loyal voters. In addition, voter trust and loyalty influence voting intentions. The more voters trust politicians, the more likely they are to vote in elections.